Back to the future: rising to the Semmelweis challenge in hand hygiene. (August 2011) - Stewardson, Andrew; Allegranzi, Benedetta; Sax, Hugo; Kilpatrick, Claire; Pittet, Didier
Hand hygiene is the single most important intervention for reducing healthcare associated infections and preventing the spread of antimicrobial resistance. This sentence begins most publications regarding hand hygiene in the medical literature. But why – as we mark 150 years since the publication of Ignaz Semmelweis' landmark monograph on the subject – do we continue to repeat it? One might be tempted to regard it as a truism. However, while tremendous progress has certainly been made in this field, a significant amount of work is yet to be done in both strengthening the evidence regarding the impact of hand hygiene and maximizing its implementation. Hand hygiene cannot yet be taken for granted. This article summarizes historical perspectives, dynamics of microbial colonization and efficacy of hand cleansing methods and agents, elements and impacts of successful hand hygiene promotion, as well as scale-up and sustainability. We also explore hand hygiene myths and current challenges such as monitoring, behavior change, patient participation and research priorities.